Ferroptosis‐inducing agents enhance TRAIL‐induced apoptosis through upregulation of death receptor 5. Issue 1 (30th August 2018) - Lee, Young‐Sun; Lee, Dae‐Hee; Jeong, So Yeon; Park, Seong Hye; Oh, Sang Cheul; Park, Yong Seok; Yu, Jian; Choudry, Haroon A; Bartlett, David L; Lee, Yong J
Abstract: Ferroptosis is considered genetically and biochemically distinct from other forms of cell death. In this study, we examined whether ferroptosis shares cell death pathways with other types of cell death. When human colon cancer HCT116, CX‐1, and LS174T cells were treated with ferroptotic agents such as sorafenib (SRF), erastin, and artesunate, data from immunoblot assay showed that ferroptotic agents induced endoplasmic reticulum (ER) stress and the ER stress response‐mediated expression of death receptor 5 (DR5), but not death receptor 4. An increase in the level of DR5, which is activated by binding to tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) and initiates apoptosis, was probably responsible for synergistic apoptosis when cells were treated with ferroptotic agent in combination with TRAIL. This collateral effect was suppressed in C/EBP (CCAAT‐enhancer‐binding protein)‐homologous protein (CHOP)‐deficient mouse embryonic fibroblasts or DR5 knockdown HCT116 cells, but not in p53‐deficient HCT116 cells. The results from in vitro studies suggest the involvement of the p53‐independent CHOP/DR5 axis in the synergistic apoptosis during the combinatorial treatment of ferroptotic agent and TRAIL. The synergistic apoptosis and regression of tumor growth were also observed in xenograft tumors when SRF and TRAIL were administered to tumor‐bearing mice. Abstract : In this study, we observed the involvement of the p53‐independent CHOP/DR5 axis in the synergistic apoptosis during the combinatorial treatment of ferroptotic agent and apoptotic agent tumor necrosis factor‐related apoptosis‐inducing ligand. These results suggest that the endoplasmic reticulum stress response plays an important role in the interplay between cell death pathways.